RESEARCH IN YOUNG DOCTORS: INVESTIGACIÓN EN MÉDICOS JÓVENES - Quiñones-Laveriano, Dante M. (2019)
Evidence-based medicine has improved the safety and efficacy of medical treatments to improve people's health; Even in public health, sufficient evidence to support preventive interventions is a special need in countries with limited budgets, since these countries cannot afford to carry out interventions without evidence of support. Continuing with this model involves two important issues: the first is that decision makers and treating physicians are able to access the best available evidence to support their interventions; likewise, to be able to differentiate good quality publications and avoid supporting their actions in methodologically deficient studies or with important biases, since this could put the patient's health at risk. Because the concept of evidence-based medicine could be considered relatively new, young doctors have some advantage in this regard, since they were trained with this present paradigm, which would make their assimilation in clinical practice in general easier than in older doctors.